Analisis Penilaian Ergonomi Postur Kerja Ketika Memasang Roda Dengan Metode Ovako Work Posture Analysis System dan Rapid Entire Body Assesment untuk Mencegah Musculoskeleal Disorders - Ramadhani, Muhammad; Rukman (Politeknik Penerbangan Makassar, 2019)
This ergonomi working posture research was done to reduce Muskuloskeletal Disorders in working activity at put the wheel in to the position in PerumPengangkutanPenumpang Djakarta (PPD) by three workers. Workers are working in bending and crouching in long periods of time so that it can cause Muskuloskeletal Disorders. The workers are generally paying less attention to body posture at work. The Rapid Entire Body Assesment (REBA) method and Ovako Work Posture Analysis System (OWAS) method is used to analyze body posture. The research was conducted by interviewing the parties concerned at the activity put the wheel in to the position for designing the working tools required